2021
DOI: 10.1111/apa.16059
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic full‐term infants born to women with chorioamnionitis may not need routine antibiotics

Abstract: Aim While infants with early‐onset sepsis require antibiotics, there is little evidence to support their routine use in asymptomatic infants exposed to maternal chorioamnionitis. We aimed to ascertain the incidence of culture‐proven sepsis in full‐term infants exposed to chorioamnionitis and to determine whether asymptomatic infants need routine antibiotic treatment. Methods This study was retrospective. Included were all full‐term infants admitted to our neonatal intensive care unit between 1 January 2017 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In our cohort, 92% of the mothers received epidural analgesia, possibly causing fever and raising the suspicion of chorioamnionitis. Furthermore, several studies have reported that the risk of EOS in well‐appearing term chorioamnionitis‐exposed neonates is low 8,11 . Hence, treating every neonate exposed to maternal chorioamnionitis could lead to overtreatment of asymptomatic neonates 12,13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our cohort, 92% of the mothers received epidural analgesia, possibly causing fever and raising the suspicion of chorioamnionitis. Furthermore, several studies have reported that the risk of EOS in well‐appearing term chorioamnionitis‐exposed neonates is low 8,11 . Hence, treating every neonate exposed to maternal chorioamnionitis could lead to overtreatment of asymptomatic neonates 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…Also, as there were no culture‐positive cases in our study, the safety of SRC for this cohort cannot be validated. Encouraged by our results and a low risk of EOS in this cohort, 8 we intend to revise the management guideline for term neonates exposed to chorioamnionitis using a quality improvement initiative and prospectively address the limitations of this study. This might improve early identification of neonates at risk of EOS based on risk categorisation, reduce unnecessary antibiotic exposure and promote mother–infant bonding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study did not include infants that were symptomatic at the time of initial partial septic work‐up, where an FBC has been shown to be of benefit 17 . Furthermore, as all infants included in the study were receiving prophylactic antibiotics, this study does not address how an FBC result would affect the management of infants, at risk of EOS, undergoing in‐hospital observation only and not receiving prophylactic antibiotics 18 …”
Section: Discussionmentioning
confidence: 99%